2005
DOI: 10.1117/1.1920212
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy for noninvasive glucose measurements

Abstract: We report the first successful study of the use of Raman spectroscopy for quantitative, noninvasive ("transcutaneous") measurement of blood analytes, using glucose as an example. As an initial evaluation of the ability of Raman spectroscopy to measure glucose transcutaneously, we studied 17 healthy human subjects whose blood glucose levels were elevated over a period of 2-3 h using a standard glucose tolerance test protocol. During the test, 461 Raman spectra were collected transcutaneously along with glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(176 citation statements)
references
References 18 publications
(18 reference statements)
5
168
0
Order By: Relevance
“…This increased laser power, from the previously used 250 mW (power density 19 mW/mm 2 ), translates directly into x12 higher Raman signal rates. Our levels compare well with the laser illumination intensities used in some other studies in vivo at a similar wavelength, such as those in work by Enejder et al, where illumination intensity of 300 mW/mm 2 was used safely [45].…”
Section: Optimised Instrumentsupporting
confidence: 88%
“…This increased laser power, from the previously used 250 mW (power density 19 mW/mm 2 ), translates directly into x12 higher Raman signal rates. Our levels compare well with the laser illumination intensities used in some other studies in vivo at a similar wavelength, such as those in work by Enejder et al, where illumination intensity of 300 mW/mm 2 was used safely [45].…”
Section: Optimised Instrumentsupporting
confidence: 88%
“…[4][5][6][7] However, because of the inevitable introduction of spectral artifacts, some researchers have found that removing the background does not improve calibration results obtained from multivariate analysis. 8 …”
Section: Background Signal In Biological Raman Spectramentioning
confidence: 99%
“…In our past research, we have developed a software method involving using a highly Raman active reference material to provide a sharp image on the CCD. 8 Using the curvature of the slit image at the center wavelength as a guide, we determine by how many pixels in the horizontal direction each off-center CCD row needs to be shifted in order to generate a linear vertical image. This pixel shift method as well as the curved-fiber-bundle hardware approach, ignores the fact that the slit image curvature is wavelength dependent.…”
Section: Image Curvature Correctionmentioning
confidence: 99%
“…There are also some proposed noninvasive optical methods, such as the floating reference method based on near-infrared optical spectroscopy, [5][6][7] and the Raman spectroscopy non-invasive blood glucose measurement system from MIT. 8,9 Cote et al also studied the correlation between the glucose levels with the depressing interference from corneal in Polarimetry. [10][11][12] But there are still two key issues not being solved for non-invasive blood glucose monitoring methodology.…”
Section: Introductionmentioning
confidence: 99%